Fa‘āliyyah Biṭaqah Būb Ab (Kartu Pop Up) Fī Tarqiyyati al-Dāfi‘u wa Aṡaruhu ila mahārah al-Kalām Fī al-Madrasah al-Ibtida’iyyah ar-Roudhoh Jember / The Influence of Pop Up Cards (Kartu Pop Up) towards Motivation and It’s Effectiveness on Speaking Skill in - Ahmad Faiz Shaleh (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
The purpose of this study was to reveal the effectiveness of PopUp Cards in increasing motivation at MI Ar-Roudhoh Jember and to determine the effect of motivation on speaking skills at MI Ar-Roudhoh Jember. Moreover, from the research results, Pop Up cards have a high level of effectiveness for students, with 82.62%. This is very effective because Pop-Ups are moving cards, and the resulting pictures are liked and liked by students. It helps teachers in student learning activities to facilitate the application of more concrete examples. We also learn that the motive variable has a significant result (0.000) and significantly affects the speaking skill variable. According to the table, because it is smaller than 0.05, we learned that the motivational variable had a vital outcome (0.289) and affected 28.9% of speaking skills. This is because motivation is the key to successful learning, a keeper of enthusiasm, and many studies prove it. Keywords: Pop Up Cards, Effectiveness, Motivation, Speaking Skills, MI Ar-Roudhoh. ملخص كانت أهداف هذا البحث لكشف فعالية بطاقة بوب أب (Kartu PopUp) في ترقية الدافع في المدرسة الإبتدائية الروضة جمبر ولكشف أثر الدافع إلى مهارة الكلام في المدرسة الإبتدائية الروضة جمبر. ونتائج البحث فإن بطاقة بوب أب يتمتع بمستوى عالٍ من الفعالية للتلاميذ بنسبة 82.62٪. وهذه الفعالية الكبيرة لأن بوب أب هي البطاقة المتحركة ونشأت الصور منها التي تعجب التلاميذ وتفرح لهم، وإنها تساعد المعلمين في أنشطة تعلم التلاميذ لتسهيل تنفيذ المزيد من الأمثلة الملموسة. وكذلك استفدنا أن المتغير الدافع له النتيجة الهامية (0،000) وهو يؤثر بشكل هام إلى المتغير مهارة الكلام. لأنه أصغر من 0،05. واستفدنا أن المتغير الدافع له النتيجة الهامية (0،289) وهو يؤثر إلى مهارة الكلام 528،9%. نظرا للجدول. وهذا لأن الدافع هو مفتاح نجاح التعليم، فينبغي علينا أن نرقي دافع التلاميذ أو الناشئين ونحفظهم من الملل الكلمات المفاتحية : بطاقة بوب أب، فعالية، الدافع ،مهارة الكلام، المدرسة الإبتدائية الروضة